2017
DOI: 10.2139/ssrn.3020820
|View full text |Cite
|
Sign up to set email alerts
|

Equity Crowdfunding in Germany and the UK: Follow-Up Funding and Firm Survival

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
(17 reference statements)
0
16
0
2
Order By: Relevance
“…In a similar vein, Hornuf, Schmitt, and Stenzhorn () investigate the determinants of follow‐up funding and firm failure after an equity crowdfunding campaign has taken place. They use data from 13 different equity crowdfunding portals and 413 firms that ran at least one successful equity crowdfunding campaign in Germany or the United Kingdom between 2011 and 2016.…”
Section: Synopses Of the Articles In The Special Issuementioning
confidence: 99%
“…In a similar vein, Hornuf, Schmitt, and Stenzhorn () investigate the determinants of follow‐up funding and firm failure after an equity crowdfunding campaign has taken place. They use data from 13 different equity crowdfunding portals and 413 firms that ran at least one successful equity crowdfunding campaign in Germany or the United Kingdom between 2011 and 2016.…”
Section: Synopses Of the Articles In The Special Issuementioning
confidence: 99%
“…Few studies, however, have focused on the outcomes of firms funded through equity crowdfunding, which is fundamentally different from reward‐based crowdfunding (Vismara, ). Notable exceptions include Drover, Wood, and Zacharakis (); Hornuf and Schmitt (); and Signori and Vismara (). In particular, these studies have examined follow‐on fundraising, failures, and exits .…”
Section: Introductionmentioning
confidence: 99%
“…Drover et al () use experimental data to investigate how different forms of crowdfunding influence venture capitalist's screening decisions; Hornuf and Schmitt () examine failure rates of equity crowdfunded firms in Germany and the United Kingdom; Signori and Vismara () focus on failures, follow‐on financing, and M&A exits in equity crowdfunding.…”
mentioning
confidence: 99%
“…The third contribution, authored by Hornuf et al (2018), explored ECFed companies that successfully concluded their campaigns on 14 different ECF platforms in UK and Germany.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, a relevant gap emerges from a review of dedicated literature. Up to now, in fact, only few scholars have investigated the post-campaign scenarios of ECFed companies by focussing their attention on the survival rate of ECFed companies and on the possibility for these companies to get following funding rounds (Di Pietro et al, 2018;Hornuf et al, 2018;Signori and Vismara, 2018;Walthoff-Borm et al, 2018) or create innovation/ growth opportunities (Eldridge et al, 2019). To the best of our knowledge, there are no studies that have investigated the post-birth growth capabilities of ECFed companies andin particularhow intellectual capital (IC) influences company growth.…”
Section: Introductionmentioning
confidence: 99%